Agency as a mode of involvement with information design - Fadel, Luciane; Coelho, António (InfoDesign, 2022)
This paper approaches agency as the primary mode of involvement with information design. We are particularly interested in the design of information in a digital interface. We consider that agency as a mode of involvement can frame the dimension of information design in a digital interface. In order to do so, the close reading method was applied to investigate how the interface supports the agency on two websites. Personal interest, points of contact, and information processing performed as analytical lenses. The findings suggest that the agency involvement with the information design supports designing the information in its concrete aspect. Information design tends to facilitate the entire scope of the agency in receiving this interface. Mastering action is the most evident due to the haptic dimension of interactivity and its immediate effect on the interface. Thus, recognizing the importance of agency involvement can benefit both the analysis and production of information design.